Concordant Oral-Genital HPV Infection in South Africa Couples: Evidence for Transmission - Vogt, Samantha L.; Gravitt, Patti E.; Martinson, Neil A.; Hoffmann, Jennifer; DSouza, Gypsyamber (Frontiers in Oncology, 2013)
Objective: Cervical cancer is a leading cause of cancer mortality in South Africa. However, little is known about oral HPV infection in high HIV seroprevalence settings. Method: 34 adult heterosexual couples attending an HIV testing center in Soweto, South Africa were enrolled. Each participant provided an oral rinse sample and genital swab, which were tested for 37 types of HPV DNA, and completed a risk behavior survey. Results: Median age was 31 years and 9% (3/34) of men and 29% (10/34) of women enrolled tested HIV-positive; median CD4 count was 437cells/mm3. Oral HPV prevalence was similar in women and men (12% vs 18%, p=0.48), and was non-significantly higher in HIV-infected vs. HIV-uninfected (23% vs. 13%, p=0.34) subjects. Most men (82%) and women (84%) reported ever performing oral sex. Median number of lifetime sexual partners was “2-5”while median number of lifetime oral sex partners was 1. Oncogenic HPV subtypes were detected in 4% of oral, 26% of penile, and 74% of vaginal samples, including HPV16 in 1%, 12%, and 21% of these samples respectively. Genital HPV prevalence was significantly higher than oral HPV prevalence (75% vs. 15%, p=